Duplicated extrahepatic duct type Vb in a patient with gallstone pancreatitis - Morgan Evans, MD; Marisa Michealson, BS; Jason McKee, MD (Elsevier, 2021)
As rates of childhood obesity rise, the frequency of laparoscopic cholecystectomy to treat gallbladder disease in the pediatric population is increasing. Knowledge of biliary anatomy and its variants is vital to performing this operation safely. Duplication of the extrahepatic biliary tree is a rare but important variant. The significance of duplicated common bile duct anatomy is important as these variations may pre-dispose patients to stone formation and obstruction. Here we present the case of an 11-year-old girl with gallstone pancreatitis and a duplicated common bile duct. The patient underwent interval laparoscopic cholecystectomy following resolution of pancreatitis. A duplicated common bile duct type Vb was identified on intraoperative cholangiogram and subsequent endoscopic retrograde cholangiopancreatography.